A Market Based Approach of Sustainable and Inclusive Growth of Tourism: A Case Study of Mwanza Tanzania (Global Journal of Management and Business Research, 2023)
The future growth of sustainable tourism and its contribution to the Tanzanian economy depends to a large extent on the entrepreneurs with knowledge and ability to supply tourists with the quality services and or products which favor inclusiveness Entrepreneurs face a challenge of understanding the customer and serve them in a sustainable way While sustainable tourism development has a close link to the environment inclusiveness literally means opening more opportunities for people to participate in tourism and results to a more fairly economic distribution of the tourism benefits across the society While it often includes people with disabilities inclusive tourism also has no clear boundaries but the services and products offered to enable enjoyment for all is what may shape the boundary define the degree of inclusivity and benefits This case examines the characteristics of visitors to Mwanza for effective and successful development and management of a regional tourism for inclusive growth